THE ROLE OF LOCAL COMMUNITIES IN PRESERVING NATURAL TOURISM : Systematic Literature Review - palan, yosephina; priyanto, Rahmat (JURNAL KEPARIWISATAAN, 2025)
The role of local communities in the preservation of a community-based attraction is vital. This research focuses on the contribution of the community in preserving nature tourism and sustainable management efforts to increase the potential of the attraction. The search results are seven articles selected by Prisma Chart with the specified inclusion and exclusion criteria. The results show that the involvement of local communities in tourism development has a vital role in achieving the goal of sustainable tourism development.  This research focuses on coordination and active participation between the government, tourism industry players and local communities. This research is expected to provide a deeper understanding of the role of local communities in nature tourism preservation as well as the application of sound governance principles.